Effect of Freeze-Drying Pre-treatment on the Properties of Activated Carbon Derived from Arabica Coffee Pulp - Effendy, Ahmad Hidayat; Setiawan, Adi; Dewi, Rozanna; Hakim, Lukman; Hasibuan, Rizqon (Reaktor, 2024)
Activated carbon is a product that has many benefits since it has a high surface area and high fixed carbon content. Currently, there is still limited research that focuses on the use of coffee pulp biomass as raw material for activated carbon due to its natural properties which poses challanges. The aim of this research is to examine the influence of the pre-treatment process using the freeze-drying method on the properties of active carbon from coffee pulp waste. The best-activated carbon products can then be applied as energy storage materials. The steps taken in this study include stages (i) washing and soaking the raw materials; (ii) drying using the freeze-drying method; (iii) pyrolysis process; and (iv) activation process. Some samples were chemically activated using a KOH solution, some were physically activated using Nitrogen at a temperature of 800 °C, and the others were activated using a mixed chemical-physical method. The results of the activated carbon characteristic test show that samples dried using a freeze dryer have quite good thermal resistance with a surface morphology that has more pores. This is supported by functional group analysis which shows a reduction in unnecessary sample compounds. This research shows that freeze-drying pre-treatment affects the properties of activated carbon and indicates that the resulting activated carbon can be used as an energy storage material.